A Landmark Approach to Aphrodisiac Property of Abelmoschus manihot (L.) - K.K. Rewatkar,; Naiyer Shahzad,; Ayaz Ahmed,; Mohd. Irfan Khan,; N. Ganesh, (International Journal of Phytomedicine, 2010)
The Abelmoschus manihot (L.) commonly reffered to as “Junglee bhindi” is widely used to control fertility, depression and anxiety in traditional Chinese medicine and has potential therapeutic benefit for cardiovascular diseases associated with diabetes mellitus. The present study is aimed to investigate the effect of 95% ethanolic extract of Abelmoschus manihot on general mounting frequency, intromission frequency, penile erection index along with body weight/organ weight and sperm count on sexually normal male mice. Two doses i.e. 100and 200 mg/kg b.w. of ethanolic extract administered to Swiss albino mice, showed pronounced anabolic and spermatogenic effect in animals of respective groups. There was a remarkable increased in sperm count and penile erection index and also improved sexual behavior of male mice by increased mount and intromission frequency. The result of the present study signatured for sexual enhancing capacity of the drug Abelmoschus manihot is an individual and also holds good aphrodisiac property when compared with standard drug. It was noticed that a 200 mg/kg b.w. dose of Abelmoschus manihot, the performance rate enhances without any side effect. Therefore, the conclusion suggestive that the Abelmoschus manihot will be a drug of choice or alternative therapy for a marketed product. Which may help the population to lead their sexual life perfectly with full of pleasure to interact body, mind and sole.